1998
DOI: 10.1002/lt.500040506
|View full text |Cite
|
Sign up to set email alerts
|

Transjugular intrahepatic portosystemic shunts and liver transplantation in patients with refractory hepatic hydrothorax

Abstract: Hepatic hydrothorax is a relatively infrequent but potentially serious complication of cirrhosis resulting from the accumulation of ascitic fluid in the chest cavity. Medical management is initially directed at controlling ascites formation, but invasive therapeutic procedures may be required if symptoms persist. The aim of this study was to report on the long-term efficacy and safety of transjugular intrahepatic portosystemic shunt (TIPS) placement to reduce portal hypertension in 12 consecutive subjects with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0
4

Year Published

2004
2004
2015
2015

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(38 citation statements)
references
References 22 publications
1
33
0
4
Order By: Relevance
“…Clinical and radiographic improvement in hydrothorax has been documented in up to 68% of patients undergoing TIPS [8,[22][23][24]. Jeffries et al [9] reported one response lasting greater than 2 years. In Table 3 Reports of chest tubes placed for hepatic hydrothorax N Successful removal TIPS Complications Mortality addition, short-term mortality in the series in which therapeutic TIPS was performed is \30% [23,24].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Clinical and radiographic improvement in hydrothorax has been documented in up to 68% of patients undergoing TIPS [8,[22][23][24]. Jeffries et al [9] reported one response lasting greater than 2 years. In Table 3 Reports of chest tubes placed for hepatic hydrothorax N Successful removal TIPS Complications Mortality addition, short-term mortality in the series in which therapeutic TIPS was performed is \30% [23,24].…”
Section: Discussionmentioning
confidence: 99%
“…Sodium restriction and diuresis are currently the mainstay of therapy [3,4,6,7]. In patients with refractory hydrothorax, recommended therapies include therapeutic thoracentesis, TIPS [8,9], and pleurodesis [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…TIPSS related HE was defined as new onset (i.e., never existed prior to TIPSS) or worsening (increased in frequency or severity of encephalopathy, compared to pre-TIPSS status). One study considered HE as TIPSS related if it occurred within 30 d of the procedure [24] ; and (2) Mortality After TIPSS. Death was evaluated as early (i.e., occurred within 45 d of the procedure) and overall (death irrespective of when the event occurred throughout the follow-up period).…”
Section: Tipss-related Complicationsmentioning
confidence: 99%
“…The procedure is often used as a bridge to liver transplantation in patients with end-stage liver disease. Since RHH is an uncommon complication of cirrhosis, most of the studies on the effectiveness of TIPSS have been limited to small numbers of patients, primarily in the form of case reports [19][20][21][22] or case series [3,14,[23][24][25][26][27][28] . Findings from these studies have varied substantially.…”
Section: Introductionmentioning
confidence: 99%
“…TIPS has been evaluated for refractory hepatic hydrothorax in numerous small noncontrolled trials 70,68,69,70,71,72,73 . On the whole, 198 patients underwent TIPS with a response rate (both complete and partial) ranging from 59-82%.…”
Section: Refractory Hepatic Hydrothoraxmentioning
confidence: 99%